Pemanfaatan Lynk.id dalam Meningkatkan Efektifitas Layanan Laboratorium - Risa Mustafa, Hanif; Seta Gilang Pratama, Amor; Mahanani, Nugrahadi; Utami, Septi; Nopiansyah, Radius (Pendidikan Sejarah FKIP Universitas JAMBI, 2025)
Jurusan SESA FKIP Universitas Jambi Laboratory is a provider of academic support facilities that can be borrowed by students. The laboratory equipment is in the form of teaching aids, multimedia devices, performance costumes, musical instruments, metal detectors, theodolites and so on. However, the service system is still manual, making it difficult for students to borrow facilities and access the laboratory. To overcome this, an innovation was made in the laboratory service system. The solution applied is the utilisation of information technology, the Lynk.id platform. Lynk.id itself resembles a simple website. The method used in this activity is the Addie Model. The results of activities to improve the effectiveness of SESA Laboratory services through the use of the Lynk.id digital platform have gone well. This activity also shows that digital technology-based service innovation through Lynk.id can be an effective solution in answering challenges in increasing the effectiveness of laboratory services and management in the university environment.